SERUM METABOLIC AND MACRO-MINERALS PROFILE IN POSTPARTUM ANESTRUS SURTI BUFFALOES TREATED WITH OVSYNCH ALONE AND IN COMBINATION WITH PRID - SAVANI, H R; KHASATIYA, C T; SAXENA, S; PATEL, S B; SINGH, V K; CHAUDHARY, S S; CHAUDHARI, C F (The Indian Journal of Animal Reproduction, 2022)
Eighteen anestrus Surti buffaloes were subjected to Ovsynch or Ovsynch plus PRID or inseminated atspontaneous estrus (n=6 in each group). Serum protein and cholesterol was higher (p0.05) between animals during the study period.
Keywords: Anestrus; Buffalo; Metabolic; Mineral; Ovsynch